Queerovski pristop k vzgoji - Tuš, Nina (Družboslovne razprave, 2014)
This article presents the concept of queer pedagogies and explains it as a frame enabling discussions about same-sex families in kindergartens and at the same time follows requirements such as criticality, objectivity and pluralism that are the foundation of preschool education. Empirical data were gathered from preschool teachers and assistant preschool teachers in 2012 by the author. The results of curriculum analysis indicate that the discussion of same-sex families could be included in the educational process at various levels. The key finding of the research is that preschool teachers and assistant preschool teachers do not include themes of same-sex families in their discussions with children. In the article, we assume that the (queer) children's story And Tango Makes Three, outlining the everyday life of a same-sex family, represents a best practice and suitable tool that would help preschool teachers and assistants present the notion of same-sex families in a way that is easily perceived by children.
Keywords: Predšolska vzgoja; Preschool education; Same-sex civil partnership; Istospolna partnerska skupnost; Pravljice; Fairy tales; istospolna družina; Richardson, Justin: In s Tango smo trije